2021
DOI: 10.1016/j.ajpath.2021.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-C Motif) Ligand 1 Derived from Tumor-Associated Macrophages Contributes to Esophageal Squamous Cell Carcinoma Progression via CCR8-Mediated Akt/Proline-Rich Akt Substrate of 40 kDa/Mammalian Target of Rapamycin Pathway

Abstract: Tumor-associated macrophages (TAMs) promote tumor progression. The number of infiltrating TAMs is associated with poor prognosis in esophageal squamous cell carcinoma (ESCC) patients; however, the mechanism underlying this phenomenon is unclear. cDNA microarray analysis indicates that the expression of chemokine (C-C motif) ligand 1 (CCL1) is up-regulated in peripheral blood monocytee derived macrophages stimulated using conditioned media from ESCC cells (TAM-like macrophages). Here, we evaluated the role of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
0
12
2
Order By: Relevance
“…Tumor-infiltrating Tregs express CCR8, whereas most Tconvs do not in a majority of cancers in humans and mice. It has been shown that CCR8 is predominantly expressed by Tregs, especially highly activated Tregs, including tumor-infiltrating ones ( 19 , 20 ), and that the interaction of CCR8 with its ligands CCL1 and CCL18 secreted from tumor cells or macrophages activates Treg cell functions ( 19 , 40 43 ). These findings on selective CCR8 expression by tumor Tregs contrast with the general finding that both Tregs and Tconvs expressing common chemokine receptors are recruited to the same inflammation site; for example, CXCR3-expressing T-bet + Tregs and Th1 cells to type 1 inflammation sites and CCR6-expressinng Tregs and Th17 cells to the type 3 inflammation environments ( 13 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-infiltrating Tregs express CCR8, whereas most Tconvs do not in a majority of cancers in humans and mice. It has been shown that CCR8 is predominantly expressed by Tregs, especially highly activated Tregs, including tumor-infiltrating ones ( 19 , 20 ), and that the interaction of CCR8 with its ligands CCL1 and CCL18 secreted from tumor cells or macrophages activates Treg cell functions ( 19 , 40 43 ). These findings on selective CCR8 expression by tumor Tregs contrast with the general finding that both Tregs and Tconvs expressing common chemokine receptors are recruited to the same inflammation site; for example, CXCR3-expressing T-bet + Tregs and Th1 cells to type 1 inflammation sites and CCR6-expressinng Tregs and Th17 cells to the type 3 inflammation environments ( 13 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, previous studies have found that cancer-related pathways could regulate the ESCC development [37,40]. For example, Fujikawa M et al [45] indicated that the interaction between stromal CCL1 and CCR8 on cancer cells promotes ESCC progression via the Akt/proline-rich Akt substrate of 40 kDa/mammalian target of rapamycin pathway.…”
Section: Discussionmentioning
confidence: 98%
“…CCR8 is the sole receptor for CCL1, and the CCL1-CCR8 axis promotes tumour activity in various malignancies. [14][15][16][17] To date, the difference between CCL1 expression at CRC primary and metastatic sites has not been elucidated. Pulmonary metastasis is the second most common metastatic site of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, down-regulated genes at liver metastatic sites related to TAMs were selected as the top of five candidate genes (Figure 1B). The CCL1 gene was selected for further study by considering the following: Among the five top candidate genes, CCL1 gene expression has the largest gap between CRC primary sites and liver metastatic sites; previous studies have demonstrated that CCL1 progresses clinically and biologically in several solid tumours, [14][15][16][17] which might also support the mechanism of altered tumour activity in our study.…”
Section: Rna Sequencing Of Resected Crc and Crlm Specimens Suggests T...mentioning
confidence: 99%